KHAZANAH TUMBUHAN DI PAPUA PADA KOLEKSI PERPUSTAKAAN PUSAT KONSERVASI TUMBUHAN- KEBUN RAYA BOGOR LIPI - Rina Munazar; Muthia Nurhayati (Fihris: Jurnal Ilmu Perpustakaan dan Informasi, 2020)
The mission of the special library for government agencies is to provide library material and access to information for the parent institution, while one of its functions is to develop collections that support the performance of the parent institution so that the library plays an important role in research activities at the Center for the Conservation of Plants-Bogor Botanical Gardens (PKT-KRB) LIPI. The natural beauty of Papua attracts researchers both from within and outside the country to conduct research on its biodiversity, including researchers from PKT-KRB LIPI, therefore libraries are supposed to provide a collection of plants in Papua that can be used as a reference for research activities. The purpose of this study is to provide information about the library collections in PKT-KRB LIPI, especially those related to plants in Papua. Through literature study, the author explores the collections in the library to find out what collections are contained in the library which contains information on plants in Papua to be discussed in detail. The results of the study show that the number of collections containing information on plants in Papua in the period of publication from 1985-2019 includes: 17 books, 10 travel reports, and 6 proceedings. Suggestions for further study are to focus on one of the endemic plants in Papua with literature studies not only on collections in the library but extending to the results of research by PKT-KRB LIPI research staff.